(untitled) (Bangladesh Journal of Medical Science, 2024)
Introduction As a minority group homosexuality poses the risk of various mental illnesses and medical comorbidities. In Malaysia, homosexuality is prohibited according to culture, law, and religion. Thus, this group is reluctant to seek help due to the negative attitude of certain healthcare professionals. Healthcare professionals’ negative attitudes towards this group may negatively impact patient care quality. This study aimed to identify predictors of health sciences students’ attitudes toward homosexuality. Materials and methods An online cross-sectional study was conducted among 307 undergraduate clinical students at a university on the east coast of Malaysia from December 2020 to February 2021. The instruments consisted of the Homosexual Attitude Scale Malay Version (HASMV), Self-Reflection and Insight Scale (SRIS), and Duke University Religion Index (DUREL). Results The mean (SD) age of participants was 22.91 (0.78) years old. The majority are female, Malay, and Muslim. Mean (SD) scores of attitudes towards homosexuality among health sciences students were 61.53 (17.06). Non-Muslims, final-year students, and those with higher self-reflection scores in central and southern Peninsular Malaysia displayed a more positive attitude towards homosexuality, as did students with a history of contact with homosexuals. Students with higher intrinsic religiosity scores were shown to be more negative towards homosexuality. Conclusion The attitude towards homosexuality of Malaysian future health practitioners leaned mostly towards the positive attitude towards homosexuality. These findings shall aid the relevant authorities in revising the curriculum to raise awareness about homosexual health, as well as arranging training programs. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1120-1128